Educating Muslim Malay Society In Confronting The Phenomenon Of Fabricated Hadith Propagation - et. al., Firdaus Khairi Abdul Kadir, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The two major sources of the religion of Islam is the Quran and Hadith. Devoid of both, Muslims will certainly stray from the path of truth. Via the promptness of information technology nowadays, the two sources of commandment turn out to be easily referenced and studied. Nonetheless, it is worrying that with the distance of the present day to the time of the Messenger of Allah, the source of the law in particular al-Hadith entails to be verified before dissemination. Currently, many queries about the hadith arise, due to the existence of those who have taken the opportunity to boost their sales or introduce certain novel act of worships that are alleged to originate from the Messenger of Allah. However, when reexamined by the contemporary scholar of hadith, it is found that the hadiths were either false or extremely feeble. In reality, what is even more unsettling is the blunder originated from the religious preacher whom involved in the spreading of false hadiths in their lectures. So much so that the public is often muddled about the legitimacy of their religious practices. With that in mind, studies on the legality of legal sources such as hadiths need to be deliberated and researched. Hence, the study was conducted to recommend pertinent resolutions to ensure that Muslims; especially in the end times, to ensure their devotion are based on Quran and al-Hadith. The methodology of the study take on archival research by scrutinizing the renowned books of evidence and eminent contemporary writings in the field of study to ensure that this study is more reliable and capable to answer existing problems. In addition, this study also employed qualitative methods via interviews with prominent leaders in the field of study along with the observations of the researcher especially in the course of this study. Upon the completion of the research, there are several findings that indicate that the phenomenon ensued due to the failure of Muslims to preserve the authenticity of the hadith by inattentively allowing some practices to be performed without any reference to the established manuscript of hadiths, resulting in some practices being made based on false hadiths.